Promising African plants - PROTA Foundation (PROTA Foundation, 2010)
Prepared in celebration of the 10th anniversary of PROTA, this book presents 25 promising plant species in terms of product development and market opportunities. The potential of three of these species – roselle, sorghum and spiderplant – has been studied in pilot projects in collaboration with grass roots organisations. The book promotes the need to conduct similar studies of the other 22 identified species.